Divorce Among Female Muslim Civil Servants: Legal Perspectives in Indonesia - Bukido, Rosdalina; Azzochrah, Nurul Azizah; Asril Amirul Zakariah,; Nur Paikah, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
Divorce among Muslim female civil servants in Indonesia carries complex social, emotional, and legal implications. This study examines the underlying causes of divorce and analyzes its impact on women from the perspective of Islamic family law and gender justice. Employing a qualitative socio-legal approach, data were gathered through semi-structured interviews with religious court judges and divorced female civil servants, alongside document analysis and field observations in four jurisdictions with high divorce rates. The findings indicate that marital breakdown is primarily driven by the absence of financial support, unequal gender roles, and dysfunctional communication within the household. Although patriarchal cultural norms were found to weaken women’s roles in household decision-making, they were not the sole determining factor. The study highlights the importance of reinterpreting Islamic legal concepts such as fasakh (annulment of marriage) and nafaqah (alimony) in light of contemporary social realities to ensure fair treatment of women. This research contributes to the academic discourse on Islamic family law by offering a contextual, experience-based understanding of divorce, particularly among working Muslim women, and advocates for a transformative legal framework that integrates gender-sensitive interpretations into both Islamic jurisprudence and state law to address divorce dynamics among Muslim female civil servants